2020
DOI: 10.1155/2020/1415947
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphonuclear Cell Chemotaxis and Suicidal NETosis: Simultaneous Observation Using fMLP, PMA, H7, and Live Cell Imaging

Abstract: Chemotaxis and the formation of suicidal neutrophil extracellular traps (suicidal NETosis) are key functions of polymorphonuclear cells (PMNs). Neutrophil extracellular traps in particular are known to be significantly involved in the severity of inflammatory and immunological disorders such as rheumatoid arthritis and Crohn’s disease. Therefore, detailed knowledge of PMNs is essential for analyzing the mechanisms involved in, and developing new therapies for, such diseases. To date, no standard method to anal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 37 publications
1
14
0
Order By: Relevance
“… 30 In accordance with the observations regarding ROS production, we found an earlier NETosis onset of 60–70 minutes for both concentrations of propofol, and ET 50 NET values were reduced by 40 minutes in both cases. These findings reflect the proven sequence from one of our previous studies, 23 and our findings are in line with several other studies. ROS production is a known activator of NETosis 41 , 42 and it has been shown that a defect in NADPH oxidase in patients suffering from chronic granulomatosis has led to an inability to generate NETs.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“… 30 In accordance with the observations regarding ROS production, we found an earlier NETosis onset of 60–70 minutes for both concentrations of propofol, and ET 50 NET values were reduced by 40 minutes in both cases. These findings reflect the proven sequence from one of our previous studies, 23 and our findings are in line with several other studies. ROS production is a known activator of NETosis 41 , 42 and it has been shown that a defect in NADPH oxidase in patients suffering from chronic granulomatosis has led to an inability to generate NETs.…”
Section: Discussionsupporting
confidence: 94%
“…The experimental setup was based on previous studies of ours. [20][21][22][23][24] In brief, whole blood was drawn from 34 healthy blood donors (Table 1) with their informed consent and as approved by the University of Regensburg's ethics committee (File number 18-1210-10) and was conducted in accordance with the Declaration of Helsinki. This blood was then anticoagulated using lithium heparin.…”
Section: Granulocyte Preparationmentioning
confidence: 99%
“…In conclusion, our experimental setup with in vitro examinations of a collagen-I-matrix proves that PMN activity sequence starts with migration before the cells undergo conformational change, start ROS production, and finally undergo NETosis. 50 Our data provide evidence that LAs in higher clinically applied concentrations have an inhibitory effect on PMN´s ability to migrate, the extent of this migration, and the ability to migrate efficiently. The time required until onset of ROS production and NETosis was reduced in a dose-dependent manner for both drugs, whereas the intensity and overall amount of ROS production and NETosis were unaffected.…”
Section: Resultsmentioning
confidence: 57%
“…The experimental setup was based on previous experiments published in [ 22 , 25 , 26 ]. To observe PMN behavior, a chemotactic assay was performed using 3D-µ-slides (ibidi© GmbH, Martinsried, Germany) according to the manufacturer’s instructions.…”
Section: Methodsmentioning
confidence: 99%